Degradable allyl Antheraea pernyi silk fibroin thermoresponsive hydrogels to support cell adhesion and growth. Issue 45 (23rd August 2021) - Wang, Boxiang; Xu, Hangdan; Li, Jia; Cheng, Dehong; Lu, Yanhua; Liu, Li
Abstract : At present, Antheraea pernyi silk fibroin (ASF) based hydrogels have wide potential applications as biomaterials because of its superior cytocompatibility. Abstract : At present, Antheraea pernyi silk fibroin (ASF) based hydrogels have wide potential applications as biomaterials because of their superior cytocompatibility. Herein, ASF is used as a nucleophilic reagent, reacted with allyl glycidyl ether (AGE) for the preparation of allyl silk fibroin (ASF-AGE). The investigation of ASF-AGE structure by 1 H NMR and FTIR are revealed that reactive allyl groups were obtained on ASF by nucleophilic substitution. A series of ASF based hydrogels are manufactured by N -isopropylacrylamide (NIPAAm) copolymerization bridged with ASF-AGE. By the silk fibroin self-assembly process, stably physical cross-linked hydrogels are formed without any crosslinking agent. These hydrogels exhibit good thermoresponsive and degradability, for which the LCST was about 32 °C, and these hydrogels can be degraded in protease XIV solution. Excellent cell proliferation, viability and morphology is demonstrated for b End.3 cells on the hydrogels by the characteristic MTT assay, CLSM and SEM. The cytocompatibility of b End.3 cells was demonstrated with excellent cell adhesion and growth on these ASF based hydrogels in vitro . These degradable and thermoresponsive ASF based hydrogels may find potential applications for cells delivery devices and tissue engineering.